2014
DOI: 10.3168/jds.2013-7836
|View full text |Cite
|
Sign up to set email alerts
|

Temporary alterations to postpartum milking frequency affect whole-lactation milk production and the energy status of pasture-grazed dairy cows

Abstract: This study investigated the immediate and long-term effects of temporary alterations to postpartum milking frequency (MF) on milk production, body condition score (BCS), and indicators of energy status in pasture-grazed cows supplemented with concentrates. Multiparous Holstein-Friesian cows (n = 150) were randomly assigned to 1 of 5 groups at calving: milked twice daily (2 ×) throughout lactation (control), or milked either once daily (1 ×) or 3 times daily (3 ×) for 3 or 6 wk immediately postpartum, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 61 publications
9
31
2
1
Order By: Relevance
“…Eslamizad et al (2010) found the milk yield and fat corrected milk yield to be higher for six times a day milkings compared to three times a day (36.82, 37.32 versus 34.56, 35.33 kg/d). Phyn et al (2014) found that different milking frequencies in early lactation affected milk yield but not milk fat or protein content. Also in the study by McNamara et al (2008), milking frequency had no influence on the milk fat and protein content.…”
Section: Structure Of Cows In Mff Groupsmentioning
confidence: 95%
“…Eslamizad et al (2010) found the milk yield and fat corrected milk yield to be higher for six times a day milkings compared to three times a day (36.82, 37.32 versus 34.56, 35.33 kg/d). Phyn et al (2014) found that different milking frequencies in early lactation affected milk yield but not milk fat or protein content. Also in the study by McNamara et al (2008), milking frequency had no influence on the milk fat and protein content.…”
Section: Structure Of Cows In Mff Groupsmentioning
confidence: 95%
“…We have also previously reported that short periods of 1× milking during early lactation had short-term positive carry-over effects on metabolic status once cows were switched to 2× milking as plasma glucose and insulin concentrations remained greater and NEFA concentrations remained lower (Phyn et al, 2014). However, only one published study has measured carryover effects of 1× milking in late lactation (Ferris et al, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…We have previously reported improvements in the metabolic status of grazing cows when milked 1× either immediately postcalving or during a period of feed restriction in early lactation Phyn et al, 2014). Plasma concentrations of glucose and insulin were greater, and nonesterified fatty acids (NEFA) were reduced, in cows milked 1× compared with those milked 2× Phyn et al, 2014), indicating a more positive energy balance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the articles used in the meta-analysis were pen studies, and two used Jersey cows and reported two different trials ( Table 1). Only a single study used lactating dairy cows on pasture 30 . The average trial duration was 220±102 milking days.…”
Section: Literature Searchmentioning
confidence: 99%